2001
DOI: 10.1046/j.1365-2699.2001.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest plant species richness in small, fragmented mixed deciduous forest patches: the role of area, time and dispersal limitation

Abstract: Aim The research aimed to investigate how plant species richness of small, fragmented forest patches changes over time. Also interactions between time and area were studied in relation to species richness. Finally, the relative importance of plant dispersal limitation on the process of species accumulation was examined by investigating how species were distributed within a regional landscape.Location Mixed deciduous forest patches in central Belgium. MethodsThe land use history of a region of 80 km 2 was recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 42 publications
8
115
1
2
Order By: Relevance
“…In addition to data from the studies in Verheyen et al (2003), data from 7 recent publications (Heinken, 1998;Graae, 2000;Graae & Sunde, 2000;Jacquemyn, Butaye & Hermy, 2001;Wulf, 2003;Brunet, 2004;Kolb & Diekmann, 2004) were used in the calculation of the CCI. The data met the same criteria as given in Verheyen et al (2003), and the same methods were used for calculating the CCI (but with opposite sign, cf.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to data from the studies in Verheyen et al (2003), data from 7 recent publications (Heinken, 1998;Graae, 2000;Graae & Sunde, 2000;Jacquemyn, Butaye & Hermy, 2001;Wulf, 2003;Brunet, 2004;Kolb & Diekmann, 2004) were used in the calculation of the CCI. The data met the same criteria as given in Verheyen et al (2003), and the same methods were used for calculating the CCI (but with opposite sign, cf.…”
Section: Introductionmentioning
confidence: 99%
“…This could also be due to an interaction between time and patch size, because plantations had greater patch sizes and were younger than the natural forests. The effects of time on species richness could not be separated from patch area, and patch area and time clearly interacted (Jacquemyn et al, 2001).…”
Section: Contribution Of Each Stand Type To Diversity Conservationmentioning
confidence: 91%
“…Studies have shown that more than a century after forests stabilize at some level of fragmentation a deficit still persists in the number of plant species that originally occupied those forests [2], and that the processes of species colonization of second-growth and fragmented forests may continue for centuries with 100-200-year-old recent forests still having lower species richness of forest herbaceous vegetation than ancient forests [2,[6][7][8]. Increase in fragmentation has also been identified as a major threat to the conservation of forest ecosystems and their functions as a whole [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%